Computer simulations of small molecules and proteins in solution - Kariyawasam Manachchige, Nilusha Lakmali (Kansas State University, 2019)
Computer simulations have been widely used in studying macromolecular systems due to a rapid increase in computer power. These simulations allow one to explore the structure, function and dynamics of biomolecules at atomistic level details and to predict unknown molecular properties. The accuracy of a computer simulation is mainly determined by the quality of the force field and the degree of sampling achieved during a simulation. Furthermore, the accuracy of calculated properties or results will depend on the methodology used to calculate these properties. Most force fields are developed by fitting the bonded and non-bonded interaction parameters to the quantum mechanically or experimentally obtained data. In contrast, our effort to develop a simple, classical, non-polarizable, force field is based on fitting parameters, especially the partial atomic charges, to reproduce Kirkwood-Buff integrals (KBIs) for solution mixtures. Kirkwood-Buff (KB) theory is a theory of solution mixtures that can be applied to solutions with any number of molecules, regardless of their size and complexity. This theory allows us to obtain the correct balance between the solute-solute and solute-solvent interactions. A Kirkwood-Buff derived force field for polyols in solution will be discussed. Fluctuation solution theory (FST) is an extension of KB theory which provides information regarding the local composition of solutions, or the deviation of local composition from bulk solution. The KBIs can be expressed in terms of particle number fluctuations and this allows us to calculate the KBIs without integrating the pair correlation function. A FST approach is used to calculate the partial molar volume and compressibility of proteins at infinite dilution without any subjective definitions of the protein volume and compressibility. These properties are solely determined using the solvent/water fluctuations in the presence and absence of the protein. Furthermore, residue-based contributions to these properties are also available and are calculated. The results are compared among different proteins and force fields to establish trends. Pressure perturbation is a powerful technique to study the hydration of macromolecules. Molecular dynamics techniques are used to identify the effect of pressure on the conformations of LacI and some variants of LacI. The lac repressor protein (LacI) is the regulatory unit of lac operon and it binds to the target site of the operon to repress the transition of the genes. The mutations studied here correspond to an experimentally known rheostat position, and we attempt to correlate the changes in activity for different mutants with the corresponding hydration changes.
Keywords: Molecular dynamics simulations; Force field; Proteins; Thermodynamics; Polyols